Integrating Solid Waste Management into Sustainable Manufacturing Systems: A Life Cycle Assessment Approach (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The study aimed to integrate solid waste management (SWM) strategies into sustainable manufacturing systems using the Life Cycle Assessment (LCA) framework to evaluate environmental performance and identify waste reduction opportunities. Conducted among selected manufacturing facilities in Bulacan, Philippines, the research employed a descriptive–analytical design supported by quantitative and qualitative data. The study focused on determining the major sources and types of solid waste, assessing their environmental impacts through LCA, and developing an integrated framework for sustainable waste management. Results revealed that most waste originated from machining, packaging, and post-processing operations, with metal and plastic wastes comprising the largest share. The Life Cycle Impact Assessment (LCIA) indicated a 32% reduction in global warming potential, a 23% decrease in resource depletion, and a 40% reduction in landfill waste after integrating SWM strategies. These improvements were achieved through source segregation, recycling, and lean-green process optimization. The developed framework emphasized four core components: waste identification and classification, LCA-based monitoring, process optimization, and continuous improvement aligned with ISO 14001:2015 and Sustainable Development Goal 12. The findings affirm that the integration of SWM and LCA enhances resource efficiency, reduces environmental impacts, and supports the transition toward circular economy practices in the manufacturing sector.